A new approach to assess drug sensitivity in cells for novel drug discovery. (3rd April 2018) - Mazzarella, Luca; Curigliano, Giuseppe
ABSTRACT: Introduction : There is a pressing need to improve strategies to select candidate drugs early on in the drug development pipeline, especially in oncology, as the efficiency of new drug approval has steadily declined these past years. Traditional methods of drug screening have relied on low-cost assays on cancer cell lines growing on plastic dishes. Recent massive-scale screens have generated big data amenable for sophisticated computational modeling and integration with clinical data. However, 2D culturing has several intrinsic limitations and novel methodologies have been devised for culturing in three dimensions, to include cells from the tumor immune microenvironment. These major improvements are bringing in vitro systems even closer to a physiological, more clinically relevant state. Areas covered : In this article, the authors review the literature on methodologies for early-phase drug screening, focusing on in vitro systems and analyzing both novel experimental and statistical approaches. The article does not cover the expanding literature on in vivo systems. Expert opinion : The popularity of three-dimensional systems is exploding, driven by the development of 'organoid' derivation technology in 2009. These assays are growing in sophistication to accommodate the increasing need by modern oncology to develop drugs that target the microenvironment